Analisis Efisiensi Home Industry Keset di Desa Karangrejo Kecamatan Purwosari Kabupaten Pasuruan - Putra, Dimas Khisbullah (Program Studi Ekonomi Pembangunan, 2023)
The purpose of this study was to determine the income of the doormat home industry and the level of efficiency or business feasibility in the doormat home industry in Karangrejo Village, Purwosari District, Pasuruan Regency. This type of research is field research (field research). The method used in this study is a quantitative descriptive method of the amount of income and the level of efficiency of the doormat home industry in Karangrejo Village, Purwosari District, Pasuruan Regency. Data collection techniques in this study were questionnaires and interviews. The analytical technique used in this research is the micro approach with the income formula (π=TR-TC) and the business efficiency formula (R/C ratio). The results of this study indicate that; 1) The total net income of the doormat home industry in Karangrejo Village is Rp. 57,235,850, with an average income of Rp. 4,088,275; 2) The intermediate level of efficiency or business feasibility in the doormat home industry is 1,23. The doormat home industry in Karangrejo Village, Purwosari District, Pasuruan Regency, is classified as profitable and feasible to run so that in the future, it has good prospects for its development.